Bringing cultured meat to market: Technical, socio-political, and regulatory challenges in cellular agriculture. (August 2018) - Stephens, Neil; Di Silvio, Lucy; Dunsford, Illtud; Ellis, Marianne; Glencross, Abigail; Sexton, Alexandra
Abstract: Background: Cultured meat forms part of the emerging field of cellular agriculture. Still an early stage field it seeks to deliver products traditionally made through livestock rearing in novel forms that require no, or significantly reduced, animal involvement. Key examples include cultured meat, milk, egg white and leather. Here, we focus upon cultured meat and its technical, socio-political and regulatory challenges and opportunities. Scope and approach: The paper reports the thinking of an interdisciplinary team, all of whom have been active in the field for a number of years. It draws heavily upon the published literature, as well as our own professional experience. This includes ongoing laboratory work to produce cultured meat and over seventy interviews with experts in the area conducted in the social science work. Key findings and conclusions: Cultured meat is a promising, but early stage, technology with key technical challenges including cell source, culture media, mimicking the in-vivo myogenesis environment, animal-derived and synthetic materials, and bioprocessing for commercial-scale production. Analysis of the social context has too readily been reduced to ethics and consumer acceptance, and whilst these are key issues, the importance of the political and institutional forms a cultured meat industry might take must also be recognised, and how ambiguities shape any emergent regulatory system. Highlights: Cellular agriculture includes tissue engineering and fermentation based approaches. Five key technical challenges with cultured meat production are made explicit. Social issue studies disproportionately focus upon ethics and consumer acceptance. New analysis of political, institutional and regulatory issues is required.